Downtown Parking and Traffic Congestion: A Diagrammatic Exposition - Richard Arnott; Eren Inci; John Rowse (European Regional Science Association (ERSA), 2012)
Through an extended numerical example, this paper develops a diagrammatic analysis of steady-state parking and traffic congestion in an isotropic downtown and provides systematic policy analysis. Unlike our previous work, the model incorporates curbside parking, garage parking, and price-sensitive travel demand in a unified setting. We examine the deadweight loss associated with underpriced curbside parking, as well as first- and second-best curbside parking capacities. We also explore the transient dynamics and stability of various downtown traffic equilibria.
Keywords: D04; L91; R41; R48; 330; cruising for parking; curbside parking; parking garages; parking policy; traffic congestion